2019
DOI: 10.1038/s41598-019-39951-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of diabetic patient’s fingernail quality to monitor type 2 diabetes induced tissue damage

Abstract: Long-term Type 2 Diabetes (T2D) affects the normal functioning of heart, kidneys, nerves, arteries, bones, and joints. The T2D gradually alters the intrinsic material properties, and structural integrity of the tissues and prolonged hyperglycemia causes chronic damages to these tissues quality. Clinically no such technique is available which can assess the altered tissues quality associated with T2D. In the present study, the microstructural characterization (surface morphology, surface roughness and density a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 57 publications
2
20
0
Order By: Relevance
“…While considerable research and drug development efforts are in place to diminish the major risks related to being diagnosed with diabetes, there are still problematic areas where adequate solutions are lacking. Diabetic patients often have a deteriorated nail standard since the breakdown of sugar can affect the quality of the nail plate [2,3]. In fact, the fingernail quality, as manifested through the calcium content, density, porosity, roughness, hardness, protein, and disulphide bond content, has been investigated as a means to monitor tissue damage in type 2 diabetes patients [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While considerable research and drug development efforts are in place to diminish the major risks related to being diagnosed with diabetes, there are still problematic areas where adequate solutions are lacking. Diabetic patients often have a deteriorated nail standard since the breakdown of sugar can affect the quality of the nail plate [2,3]. In fact, the fingernail quality, as manifested through the calcium content, density, porosity, roughness, hardness, protein, and disulphide bond content, has been investigated as a means to monitor tissue damage in type 2 diabetes patients [3].…”
Section: Introductionmentioning
confidence: 99%
“…Other components of the nail plate are water (7-25%), lipids (0.1-1.0%), and calcium [5]. The importance of calcium in the keratinized structure of the nail has persistently been investigated [6] and its depletion in the nail plate has been demonstrated in diabetes patients [3]. Additionally, clinical studies have shown that the oral intake of silicon supplements can significantly reduce nail brittleness [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research poses an interesting avenue for the exploration of secondary complications due to T2DM, with a potential to translate the changes observed within fingernail plates into an early and noninvasive diagnostic mechanism in the future. 73 Coopman et al 74 also investigated fingernails, this time using ATR FT-IR spectroscopy as a tool for assessing glycation in diabetics. Fingernail clippings were obtained and analyzed from 105 healthy individuals and 127 individuals with T2DM.…”
Section: Monitoring Novel Biomarkers For Indicating Diabetesmentioning
confidence: 99%
“…Our previous study have shown that the microstructural and macromolecular characteristics of fingernails are degraded in patients with T2DM [17]. Accordingly, we have hypothesized that the fingernail plate has the potential to serve as a potential surrogate marker to predict bone damage in diabetes because of the following reason: (i) The major constituent of fingernail plate (Keratin, present in ±85%) is also prone to glycation [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%